2011
DOI: 10.1071/mf10286
|View full text |Cite
|
Sign up to set email alerts
|

Using species distribution models to infer potential climate change-induced range shifts of freshwater fish in south-eastern Australia

Abstract: Abstract. There are few quantitative predictions for the impacts of climate change on freshwater fish in Australia. We developed species distribution models (SDMs) linking historical fish distributions for 43 species from Victorian streams to a suite of hydro-climatic and catchment predictors, and applied these models to explore predicted range shifts under future climate-change scenarios. Here, we present summary results for the 43 species, together with a more detailed analysis for a subset of species with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 43 publications
6
130
0
Order By: Relevance
“…In contrast, several cool-water native species, including river blackfish (Gadopsis marmoratus) and two-spined blackfish (G. bispinosus), will likely contract in range towards more southerly or higher altitude streams (e.g. Bond et al 2011).…”
Section: Water Temperaturementioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, several cool-water native species, including river blackfish (Gadopsis marmoratus) and two-spined blackfish (G. bispinosus), will likely contract in range towards more southerly or higher altitude streams (e.g. Bond et al 2011).…”
Section: Water Temperaturementioning
confidence: 99%
“…Several studies have demonstrated the importance of cease-to-flow events in excluding certain species from some rivers (e.g. Dodds et al 2004;Bond et al 2010Bond et al , 2011. Such patterns are likely to arise from both direct habitat loss (drying) and the rapid changes in water quality (increasing temperatures and decreased dissolved oxygen) when flows cease (Boulton and Lake 1990).…”
Section: Freshwater Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as mentioned above, the potential effects of altered hydrological 520 regimes (e.g., increased frequency of drought) and higher temperatures are well documented, and are likely drivers of change in species distributions. Statistical models linking historical and current distributional information to hydro-climatic and catchment data in freshwater ecosystems have predicted general shifts in species distributions towards higher altitudes and higher latitudes (e.g., Bond et al 2011).…”
mentioning
confidence: 99%